FLEXIBILITY: AN ISLAMIC PERSPECTIVE ON CONSUMER BEHAVIOR - Agung Adi Putra, Rifky; Khoiril Vikri, Alfan (ISTISMAR, 2019)
or show-off conduct. In his book The Theory of Leisure Class, published in 1899, Veblen examined ostentatious consumption, which is comparable to modern-day flexing. Social media's significant impact on people's views and attitudes makes it impossible to separate the flexing phenomenon, which has recently emerged as an intriguing topic of conversation in society. Furthermore, lying and fraud are linked to flexing. Analyzing the causes of flexing and how Islamic consumer behavior theory views this activity are the goals of this study. A content analysis approach combined with a qualitative research methodology is the methodology employed. According to the findings of this study, flexing is caused by five factors: boosting one's selfesteem or self-image; finding a spouse from a particular class; using flexing as a marketing signal; the environment and personality of flexing character; and lacking empathy for others. Flexing is also viewed as not being consistent with the conduct of Islamic consumers since it goes against the ethics, standards, and principles of consumption as well as the arguments made in the Al Quran and from hadith of propet Muhammad